2010
DOI: 10.1007/s12665-010-0803-0
|View full text |Cite
|
Sign up to set email alerts
|

A GIS approach for the assessment of groundwater quality in Wadi Rabigh aquifer, Saudi Arabia

Abstract: A classification approach has been implemented in the present work by integrating traditional water sample analysis methods and Geographic Information System (GIS) capabilities in order to classify zones with acceptable groundwater quality for drinking. GIS extrapolation capabilities with their multi-conditional layering facilities were integrated together in order to assess in the determination of areas suitable for drinking purposes. This technique was implemented in Wadi Rabigh, Western Saudi Arabia, due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The first one is situated in the lower region of Haqaq's spring towards the intersection with the bridge of Al Nuwabi. In this area, the depth of saturated area varies from 10-16 m and the other one is located in Al Nuwabi Wadi, an area where the thickness of the saturated area ranges between 20 and 35 m (El-Hames et al, 2011). El-Hames (2005) found that, zones with high groundwater potential are situated mostly in the alluvial part of the catchment, which form the Wadi Hishash in the middle-upper boundary and Wadi Madrakah at the higher boundary.…”
Section: Western Region (Wadibasin)mentioning
confidence: 91%
“…The first one is situated in the lower region of Haqaq's spring towards the intersection with the bridge of Al Nuwabi. In this area, the depth of saturated area varies from 10-16 m and the other one is located in Al Nuwabi Wadi, an area where the thickness of the saturated area ranges between 20 and 35 m (El-Hames et al, 2011). El-Hames (2005) found that, zones with high groundwater potential are situated mostly in the alluvial part of the catchment, which form the Wadi Hishash in the middle-upper boundary and Wadi Madrakah at the higher boundary.…”
Section: Western Region (Wadibasin)mentioning
confidence: 91%
“…Geographic information system (GIS) has become a top field of study owing to its several applications in different organizations in various fields [1]. Studies dedicated to it have been carried out in Saudi Arabia concerning GIS improvements, uses, and developments; remote sensing; determination of rainfall; management of floods; public safety; and urban planning [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Literature exhibited that extensive work has been conducted in this area (Mukherjee et al, 2005;Shah and Mistry, 2013;Venkateswaran and Vediappan, 2013;Singh et al, 2015;Narayanamurthi, 2018). In Saudi Arabia, the assessment of groundwater suitability for irrigation has been well received by many researchers (Al-Harbi, 2009;FAO, 2009;El-Hames, 2010;Khashogji and Maghraby, 2012;Al-Hasawi and Hussein, 2012). AlAhmadi (2012) stated that there are growing demands for groundwater usage due to increased anthropogenic activities associated with population growth.…”
Section: Introductionmentioning
confidence: 99%